DEVELOPMENT AND SIMULATION OF AN AUTONOMOUS VEHICLE SYSTEM FOR AIRCRAFT INSPECTION WITH COMPUTER VISION - Yohanes Pardomoan, Gerald
Visual inspection for aircraft maintenance is one of the most frequently performed procedures in the maintenance, repair, & overhaul (MRO) industry to ensure the airworthiness of an aircraft. In today's modern technology, the MRO industry uses a micro quadrotor combined with computer vision technology to carry out visual inspections because it is considered easier and faster when compared to the manual approach.